Future Selves: Career choices of young disabled people - Shah, Sonali; Pascall, Gillian; Walker, Robert (2006)
There is growing recognition that gaining the views of young people is crucial for understanding issues that affect their lives. However, to date, very little is known about the way in which disabled children, make sense of their identities, and create a sense of their past and their imagined futures over time. This three year study, funded by the European Social Fund, and conducted by Dr Sonali Shah and colleagues at the University of Nottingham, used various methods to explore how physically disabled students, in full-time special or mainstream education, make choices concerning their occupational futures. It identified the factors that shape their educational and career related choices and chances, and explored how social relations, social processes, and social policies influenced the extent to which their aspirations were achieved. This study presents disabled children and young people as critical social actors who are telling their own stories of how social structures and processes shape their choices and aspirations for their future selves. It illustrates the importance of consulting children and young people about issues concerning their lives, and not rely solely on adults’ conceptions of childhood. The young disabled people’s experiences and views can be used to develop a new flexible system which offers the benefits of mainstream and special education, and facilitates young disabled people’s self-determination to make choices to participate in and contribute to their independent futures.